2019
DOI: 10.1186/s12888-018-2007-1
|View full text |Cite|
|
Sign up to set email alerts
|

After the Fort McMurray wildfire there are significant increases in mental health symptoms in grade 7–12 students compared to controls

Abstract: BackgroundIn order to examine the impact of disasters on adolescent mental health, this study compared population mental health survey data from two communities in Alberta, Canada: Fort McMurray, which experienced a major natural disaster, and Red Deer, which did not.MethodsData from 3070 grade 7–12 students from Fort McMurray, Alberta, Canada (collected in 2017, 18 months after the 2016 wildfire) was compared with data from 2796 grade 7–12 students from Red Deer, Alberta, Canada (collected in 2014). The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 48 publications
1
68
1
4
Order By: Relevance
“…Additionally, these findings in the past month are generally consistent with the rate of suicidal ideation in the control area. 38 Furthermore, 17.2% of 14 to 18-year-olds in a general community sample were found to have suicidal ideation, 40 and the estimated lifetime prevalence of suicidal ideation in youths aged 13-17 years has been reported to be 12.1%, 41 similar to the findings of the present study. In a survey on suicidal ideation in children in Japan aged 7-15 years, 414.8% of the responses to the statement "I don't think life is worth living" on the DSRS-C were "Mostly" and "Sometimes", respectively; this was nearly identical to the results of the present survey.…”
Section: Suicide Risk and Related Factorssupporting
confidence: 85%
“…Additionally, these findings in the past month are generally consistent with the rate of suicidal ideation in the control area. 38 Furthermore, 17.2% of 14 to 18-year-olds in a general community sample were found to have suicidal ideation, 40 and the estimated lifetime prevalence of suicidal ideation in youths aged 13-17 years has been reported to be 12.1%, 41 similar to the findings of the present study. In a survey on suicidal ideation in children in Japan aged 7-15 years, 414.8% of the responses to the statement "I don't think life is worth living" on the DSRS-C were "Mostly" and "Sometimes", respectively; this was nearly identical to the results of the present survey.…”
Section: Suicide Risk and Related Factorssupporting
confidence: 85%
“…A number of studies suggest mental health effects of wildfire disasters on children. Surveys of the middle and high school students in a small Canadian city, 18 months after a large wildfire caused evacuation of the entire city, showed elevated rates of depressive symptoms among youth in that city compared to youth in a control city [ 61 , 62 ]. It is worth noting, however, that these effects cannot be clearly attributed to wildfire smoke as the trauma associated with widespread evacuation likely contributes to mental health.…”
Section: Health Effects Of Other Aspects Of Wildfire Disastersmentioning
confidence: 99%
“…Significant mental health problems associated with wildfire disasters have been documented. For example, a study of Fort McMurray residents following the Horse River fire showed increased incidences of anxiety, depression, and suicidal thoughts (Cherry and Haynes 2017;Brown et al 2019). With predicted increases in future fire activity and a growing population, we may very well expect that public health problems, health care costs, health expenditures, and mortalities associated with wildfire may rise in the future.…”
Section: Healthmentioning
confidence: 99%